MALARIA PREVALENCE RISK FACTORS IN PREGNANT WOMEN IN THE WORK AREA OF KOTARAJA HEALTH CENTER JAYAPURA CITY - Mulyani, Wiwiek (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2022)
Pregnant women are the adult age group with the highest risk of contracting malaria. The purpose of this study was to determine the risk factors for the incidence of malaria in pregnant women. This type of research is observational using a case control study design. The population was 522 pregnant women who were positive for malaria and negative for malaria recorded in the health center register in 2013. The sample was 80 pregnant women consisting of 40 pregnant women positive for malaria and 40 pregnant women negative.The results showed that there was no relationship between the habit of going outside at 18.00 - 20.00 with the prevalence of malaria (p value 0.154), there was no relationship between the habit of wearing long clothes outside the home and the prevalence of malaria (p value 1000), there was no relationship between the habit of wearing clothes every day. mosquito repellent while sleeping with malaria prevalence (p value 1000), there is no relationship between the habit of using mosquito nets while sleeping with malaria prevalence (p value 0.115), there is no relationship between the habit of opening windows at night at 18.00 – 20.00 with the prevalence of malaria (p value 0.115). value 0.431), there is a relationship between the presence of wire gauze on ventilation with malaria prevalence (p value 0.000).This study concluded that the variable associated with malaria prevalence was the presence of gauze on ventilation.